Insight into the phylogeny and metabolic divergence of Monascus species (M. pilosus, M. ruber, and M. purpureus) at the genome level - Zhang, Zhiyu; Cui, Mengfei; Chen, Panting; Li, Juxing; Mao, Zhitao; Mao, Yufeng; Li, Zhenjing; Guo, Qingbin; Wang, Changlu; Liao, Xiaoping; Liu, Huanhuan (Frontiers in Microbiology, 2023)
Species of the genus Monascus are economically important and widely used in the production of food colorants and monacolin K. However, they have also been known to produce the mycotoxin citrinin. Currently, taxonomic knowledge of this species at the genome level is insufficient. Therefore, this study presents high-resolution phylogenetic analyses based on genomes. Through the analysis of the average nucleic acid identity of the genomic sequence and the whole genome alignment, it was deduced that all the included 15 Monascus strains should be classified into two distinctly evolutionary clades, namely the M. purpureus clade and the M. pilosus-M. ruber clade. Subsequently, the study constructed a pan-genome of Monascus by reannotating all the genomes and identifying a total of 9539 orthologous gene families. Phylogenetic trees were constructed based on 4589 single copy orthologous protein sequences and all the 5565 orthologous proteins, respectively. The results clearly revealed a high homology between M. pilosus and M. ruber, and their distant relationship with M. purpureus. Moreover, gene ontology enrichment showed that the M. pilosus-M. ruber clade had more orthologous genes involved with environmental adaptation than the M. purpureus clade. Compared to Aspergillus oryzae, all the Monascus species had a substantial gene loss of carbohydrate active enzymes. Potential allergenic and fungal virulence factor proteins were also found in the secretome of Monascus. Furthermore, this study identified the pigment synthesis gene clusters present in all included genomes, but with multiple nonessential genes inserted in the gene cluster of M. pilosus and M. ruber compared to M. purpureus. The citrinin gene cluster was found to be intact and highly conserved only among M. purpureus genomes. The monacolin K gene cluster was found only in the genomes of M. pilosus and M. ruber, but the sequence was more conserved in M. ruber. This study provides a paradigm for phylogenetic analysis of the genus Monascus, and it is believed that this report will lead to a better understanding of these food microorganisms in terms of classification, metabolic differentiation, and safety.